Potential study of the relationship between maintenance manual and post occupancy evaluation residential building / Nur Syuhaida Bakharun - Bakharun, Nur Syuhaida (Faculty of Architecture,Planning and Surveying, 2014)
Nowadays, modern society has introduced to a new era of developed construction industry.Although the technology is more advance, but the facts that the building needs to fulfil users requirement and comfort is still remain the same. In order to obtain a good building performance, maintenance programmed that are regularly done by the management team should be based to the guideline in maintenance manual. Residential building in Malaysia has a lack of use of guidelines in maintenance manual when manage the building. While Post Occupancy Evaluation (POE) as an evaluation to get the view of the users is almost unheard and not practice widely in Malaysia. Post Occupancy Evaluation (POE) has brought a new dimension in evaluating building performance by auditing user feedbacks. Post-occupancy evaluation (POE) of buildings is vitally needed to ensure that building performance of government and public buildings and facilities is sustained. POE of buildings is of utmost importance in building performance evaluation, as it consist the technique that is used to evaluate whether a building meets the users requirements. By using occupants as a benchmark in evaluation, the potential for improving the performance of a building is enormous. However,there are inconsistencies in the actual performance criteria and parameters for building performance evaluation. Building experts adopt different performance evaluation criteria and parameters for different POE projects, limiting the POE findings to a single circumstance and denying the prospect for comparison with other buildings. POE also disregards the views of users on what performance criteria and parameters that needs to be considered in building performance evaluation. The findings of this research can greatly benefit the construction industry particularly the architects, building developers, facilities managers and building owner as for the first time there is a clear guideline on what performance criteria and parameters that require consideration and emphasis when designing, constructing, and managing buildings.